Methane Production from Gas Hydrate Deposits through Injection of Supercritical CO2 - Matthias Haeckel; Elke Kossel; Nikolaus Bigalke; Christian Deusner (Energies, 2012)
The recovery of natural gas from CH4-hydrate deposits in sub-marine and sub-permafrost environments through injection of CO2 is considered a suitable strategy towards emission-neutral energy production. This study shows that the injection of hot, supercritical CO2 is particularly promising. The addition of heat triggers the dissociation of CH4-hydrate while the CO2, once thermally equilibrated, reacts with the pore water and is retained in the reservoir as immobile CO2-hydrate. Furthermore, optimal reservoir conditions of pressure and temperature are constrained. Experiments were conducted in a high-pressure flow-through reactor at different sediment temperatures (2 °C, 8 °C, 10 °C) and hydrostatic pressures (8 MPa, 13 MPa). The efficiency of both, CH4 production and CO2 retention is best at 8 °C, 13 MPa. Here, both CO2- and CH4-hydrate as well as mixed hydrates can form. At 2 °C, the production process was less effective due to congestion of transport pathways through the sediment by rapidly forming CO2-hydrate. In contrast, at 10 °C CH4 production suffered from local increases in permeability and fast breakthrough of the injection fluid, thereby confining the accessibility to the CH4 pool to only the most prominent fluid channels. Mass and volume balancing of the collected gas and fluid stream identified gas mobilization as equally important process parameter in addition to the rates of methane hydrate dissociation and hydrate conversion. Thus, the combination of heat supply and CO2 injection in one supercritical phase helps to overcome the mass transfer limitations usually observed in experiments with cold liquid or gaseous CO2.